IT INVENTORY QUALITY AND BUSINESS PERFORMANCE IN INDONESIAN BONDED ZONES: THE MEDIATING ROLE OF AIS EFFECTIVENESS - Anggi Prastyono; Raditya Hendra Pratama (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2026)
This study aims to analyze the role of IT inventory quality and information quality in optimizing the business performance of companies in bonded zones, with Accounting Information System (AIS) effectiveness serving as a mediating variable. Despite their vital contribution to national exports, these companies often face suboptimal business performance due to challenges in effective AIS management. Employing a quantitative approach, this study utilizes a survey design with 166 respondents comprising professionals from bonded zone companies in Banten Province and officials from the Directorate General of Customs and Excise (DJBC). The data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results indicate that IT inventory quality has a significant positive effect on both information quality and AIS effectiveness. Furthermore, AIS effectiveness is proven to directly enhance business performance. A key finding reveals that while information quality does not directly influence business performance, it exerts a positive and significant impact when mediated by AIS effectiveness. The primary implication of this study is that bonded zone companies should prioritize enhancing AIS effectiveness, as it serves as a crucial mediator that translates investments in IT and information quality into improved business performance.